THE FIQH PARADIGM OF SUSTAINABLE DEVELOPMENT - Addiarrahman (Universitas Islam Indonesia, 2019)
The paradigm of fiqh that is currently developing has not been able to answer the demands of sustainable development that has become a global agenda. The weakness of the fiqh perspective is because it uses the perspective of a third person who positions Al-Quran as the object of interpretation. This paper uses a second-person perspective and social system paradigm. These two perspectives form the fiqh paradigm of sustainable development. Based on this paradigm, the problems that become the priorities of sustainable development are understood as the excesses of dominating cognitive (subjective) relations that encourage humans to be individualistic and materialistic. This paper offers the importance of trans-cognitive (trans-subjective) relations that control recognition (subjective) relations and cognitive relations. Furthermore, in trans-cognitive relations, Al-Quran is positioned as a communicative act (speech act) of God to humans.